Patologia we wdrażaniu nowych technologii w postępowaniupodatkowym na przykładzie obowiązków nałożonych na pełnomocników zawodowych w postępowaniu podatkowym - Pietrasz, Piotr (PRAWO i WIĘŹ, 2025)
The purpose of the paper is to demonstrate the deficiency of legal constructions, as well as their interpretations, in force in tax proceedings regulated by the Tax Ordinance, which, in the period before 1 January 2025, introduced the obligation for attorneys who are advocates, legal advisers or tax advisers to use an electronic address (address for electronic delivery) in the course of these proceedings. Computerisation and the associated technicisation of the law, including procedural law, contribute to the emergence of completely new, hitherto unknown problems. The author of the paper thinks that, in principle, the statutory solutions introduced to maximise the spread of electronic service in legal transactions and even obliging certain categories of entities to have the necessary instruments to ensure the service of letters by electronic means should be supported.